The persistence of local caudillos in Latin America : the case of Vicky Barahona in Santiago de Chile (2000-2016) - Došek, Tomáš (2025)
This article examines territorial unevenness of subnational democracy in Latin American unitary countries. While current research has focused almost exclusively on subnational regimes in federal states, existing theories face several limitations when “travelling” to the local level in unitary countries. The goal of this paper is to explain the continuity of local caudillos in office in urban settings. Contrary to the prevailing interaction-based explanations present in the literature, I propose a theoretical framework that focuses on local factors, the concept of local caudillo and the exercise of power (informal political practices). I argue that to secure their continuity in office, local caudillos need to pursue simultaneously three basic goals: foster their electoral base, control local political opposition, and neutralize other social and political actors. Based on extensive fieldwork, I illustrate this argument with a single-country study of one of the extreme cases of local caudillos, Vicky Barahona in Renca, Chile (2000–2016).